Hospital volume and outcomes of robot‐assisted partial nephrectomy. (11th January 2018) - Xia, Leilei; Pulido, Jose E.; Chelluri, Raju R.; Strother, Marshall C.; Taylor, Benjamin L.; Raman, Jay D.; Guzzo, Thomas J.
Abstract : Objective: To evaluate the impact of hospital volume on outcomes of robot‐assisted partial nephrectomy (RAPN). Materials and Methods: Patients with renal cell carcinoma who underwent RAPN between 2010 and 2013 were identified in the National Cancer Database. Hospital yearly RAPN volume was categorized into groups by sorting patients as closely as possible into five groups of equal size (quintiles): very low; low; medium; high; and very high volume. Outcomes included 30‐day mortality, 90‐day mortality, open conversion, prolonged length of hospital stay (PLOS; defined as >3 days), 30‐day readmission rate, and positive surgical margin (PSM) rate. Unadjusted analyses and multivariable logistic regressions were used to compare outcomes. Sensitivity analyses with hospital volume considered as a continuous variable were also performed. Results: A total of 18 724 RAPN cases were included. Hospital volume quintiles were: very low volume, 1–7 cases ( n = 3 693); low volume, 8–14 cases ( n = 3 719); medium volume, 15–23 cases ( n = 3 833); high volume, 24–43 cases ( n = 3 649); and very high volume, ≥44 cases ( n = 3 830). There was no significant difference in 30‐day or 90‐day mortality among the five groups. Multivariable logistic regression analysis (reference: very low volume) showed that higher hospital volume was associated with lower odds of conversion (low [odds ratio OR: 0.88; P = 0.377]; medium [OR: 0.60; P = 0.001]; high [OR: 0.57; P < 0.001]; very high [OR: 0.47; P < 0.001]), lower odds of PLOS (low [OR: 0.93; P = 0.197], medium [OR: 0.75; P < 0.001]; high [OR: 0.62; P < 0.001]; very high [OR: 0.45; P < 0.001]), and lower odds of PSMs (low [OR: 0.76; P < 0.001]; medium [OR: 0.76, P < 0.001]; high [OR: 0.59; P < 0.001]; very high [OR: 0.34; P < 0.001]). Sensitivity analyses confirmed increasing hospital volume (per 1‐case increase) was associated with lower odds of conversion (OR: 0.986; P < 0.001), PLOS (OR: 0.989; P < 0.001) and PSMs (OR: 0.984; P < 0.001). A difference in 30‐day readmission rate was found in unadjusted analysis but not in adjusted analyses. Conclusion: Undergoing RAPN at higher‐volume hospitals may have better peri‐operative outcomes (conversion to open and LOS) and lower PSM rates. Future studies are needed to explore the detailed components that lead to the superior outcomes in higher‐volume hospitals.